Whitney Multiapproximation (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this article we  prove  that Whitney  theorem  for  the  value of the  best  multiapproximation of a function   by algebraic multipolynomial  of degree .